Synthesis and Adsorption Application of In Situ Photo-Cross-Linked Electrospun Poly(Vinyl Alcohol)-Based Nanofiber Membranes - KAHRAMAN, MEMET VEZİR (SPRINGER INTERNATIONAL PUBLISHING AG, 2015)
Poly(vinyl alcohol)/maleic anhydride/acryloyl thioamide monomer (PVA/MA/ATM) nanofiber membranes (NFm) were synthesized by a combination of UV radiation and an electrospinning technique. The PVA/MA/ATM NFm were characterized by Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), Brunauer-Emmert-Teller (BET) analysis, scanning electron microscopy (SEM), and energy dispersion spectrometry (EDS). These membranes were used for adsorption-desorption of platinum (Pt(IV)) and palladium (Pd(II)) from a fire assay (FA) leaching waste solution, and the effect of process parameters such as pH of solution, contact time, NFm dosage, temperature, and adsorption isotherms and kinetics studies on the recovery of Pt(IV) and Pd(II) from the waste solution were investigated. The adsorption equilibrium data fit better using the Langmuir model than the Freundlich model. Maximum adsorption capacities, Q(max), at 45 degrees C were found to be 69.93 and 112.36 mg/g for Pt(IV) and Pd(II), respectively. The activation energies (E-a) of Pt(IV) and Pd(II) were 27.90 and 20.29 kJ/mol, respectively. The best desorption reagent was a 1.0 M HCl-1.0 M thiourea (TU) solution for both Pd(II) and Pt(IV). Reusability studies showed that the adsorption capacity can remain up to 90 % after five times of usage. This study provides a promising NFm with an effective adsorption property for Pt(IV) and Pd(II) ions.
Keywords: Electrospinning; Nanofiber; Thioamide; Adsorption; Platinum; Palladium; SPENT AUTOMOTIVE CATALYSTS; POLY VINYL ALCOHOL; HEAVY-METAL IONS; AQUEOUS-SOLUTIONS; SELECTIVE ADSORPTION; RECOVERY; PLATINUM; PALLADIUM(II); GOLD; CEMENTATION